Medical Students’ Reflection on Interprofesional Education with Nursing Students - Hasibuan, Shinta Yuliana; Tahulending, Peggy; Suryadinata, Neneng (GLOBAL HEALTH SCIENCE GROUP, 2024)
Interprofessional education (IPE) is expected to help future health professionals prepare for collaborative roles between doctors and nurses. Therefore, IPE learning needs to be provided in the learning process of medical and nursing students. Objective: he purpose of this study was to see the effectiveness of IPE learning in medical students. The method used was qualitative content analysis method on self-reflection documents. Method: The population in this study were first-year medical students who participated in IPE learning, using total sampling of 157 respondents. Data were analyzed by qualitative content analysis method on self-reflection documents done by students. Results: The results obtained were three themes namely positive experiences, negative experiences and learning outcomes. Conclusions: IPE learning can encourage the development of relationships between students and the profession of doctors and nurses.